LANGUAGE STYLE USED IN J.K. ROWLING’S HARRY POTTER AND THE CURSED CHILD - Resa Ferara Jamal; Nasrum Nasrum (Elite : English and Literature Journal, 2018)
This research discusses about Language Style Used in J.K. Rowling’s Harry Potter And The Cursed Child. The aim of this research is to find out the kind of language styles used by Albus and the social factors that influence his utterances in this novel. The researchers applied sociolinguistics approach and Martin Joos’ theory in providing the data. This research used note taking as the instrument. The findings show that Albus used 5 language styles such as: frozen style, formal style, consultative style, casual style and intimate style. The findings also reveal social factors influence the using of language style.